The hematological responses of Indonesian elite rowing athletes to different altitude training protocols - Dede Rohmat Nurjaya; Angga M Syahid; Pipit Pitriani; Herdiansyah Agus; Gafur Ammar Santoso; Bayu Santoso; Dito Dwi Cahyo (Journal of Coaching and Sports Science, 2026)
Background: Altitude training is widely used to improve endurance performance through hematological adaptations, but inter-individual variability is substantial, and responses among Southeast Asian athletes are poorly documented. Aims: This study compared hemoglobin, hematocrit, and reticulocyte dynamics in Indonesian elite rowers undergoing continuous high-altitude (HA) versus intermittent Pangalengan (PGL) protocols to characterize temporal adaptation patterns, identify predictive biomarkers, and inform protocol optimization. Methods: A total of 23 national-team rowers (8 females, 15 males) completed a 33-day longitudinal observational study at 2,434 m. Blood samples were collected at baseline (T0), post-exposure (T1, day 22), and recovery (T2, day 31). The HA group (n=12) remained continuously at altitude; the PGL group (n=11) made periodic normoxic descents. Data were analyzed using mixed-model repeated-measures ANOVA and correlation analyses. Ethical approval was obtained before data collection in accordance with the Declaration of Helsinki. Results: Contrary to expectations, the HA protocol produced significant hemoglobin reductions (males: −3.78%, p=0.008), whereas the PGL protocol elicited positive adaptations (males: +4.69%, p=0.026). Negative responders constituted 75% of the HA group versus 9.1% of the PGL group (χ²=11.52, p=0.003). Baseline ferritin did not predict hemoglobin responses (r=−0.122, p=0.579). Conclusion: Protocol design, particularly the inclusion of normoxic recovery periods, was a stronger determinant of hematological adaptation than individual iron stores or sex. These findings affirm the live-high-train-low principles across diverse populations and support recovery-oriented protocols for Indonesian elite rowers.